PENGEMBANGAN MODEL PERLINDUNGAN HUKUM TERHADAP HARTA BENDA WAKAF SEBAGAI ASET PUBLIK DI KECAMATAN WIRADESA KABUPATEN PEKALONGAN - Achmad Irwan Hamzani (Harmoni, 2016)
To meet the legal aspects, waqf endowments that must be put up in AIW/ APAIW, registered, and announced to the public. The implementation of the endowments must be in accordance with shari’ah and legislation. The practice of waqf in District Wiradesa Pekalongan tend not in accordance with the legislation. The number of waqf property are fairly large and generally in the form of land and buildings. Departing from this fact, this research aims to describe the implementation of endowments in the District Wiradesa and formulate legal safeguards against waqf property as a public asset in the District Wiradesa. This research is a field research. The approach is sociological, so it can be regarded as an empirical legal research. The collection of data was done through observation and interviews. Data were analyzed by using interpretation and induction method. The results of this study indicate factors that influence the low administration of waqf property and the lack of understanding regulations as well as the lack of socialization. The appropriate legal means to protect objects of waqf is the presence of a set of laws based on local wisdom, namely through the preparation of regional regulation as the essence of the legal formulation.